2015
DOI: 10.1039/c4cc06864e
|View full text |Cite
|
Sign up to set email alerts
|

Palladium catalyzed Csp2–H activation for direct aryl hydroxylation: the unprecedented role of 1,4-dioxane as a source of hydroxyl radicals

Abstract: A novel strategy for direct aryl hydroxylation via Pd-catalysed Csp(2)-H activation through an unprecedented hydroxyl radical transfer from 1,4-dioxane, used as a solvent, is reported with bio relevant and sterically hindered heterocycles and various acyclic functionalities as versatile directing groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…Solvent screening to get a better yield of 3 aa was unsuccessful (entries 6-11). In the presence of a basic additive such as NaOAc and Et 3 N the reaction did not proceed (entries 12,13). Interestingly, by changing the additive from PTSA to CF 3 COOH (1 equiv.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent screening to get a better yield of 3 aa was unsuccessful (entries 6-11). In the presence of a basic additive such as NaOAc and Et 3 N the reaction did not proceed (entries 12,13). Interestingly, by changing the additive from PTSA to CF 3 COOH (1 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…[4] These strategies are mainly: (i) transition-metal-catalyzed CÀO cross-coupling of 2haloanilides leading to benzoxazole motif (Scheme 1a); [5][6][7] (ii) copper-catalyzed intermolecular domino CÀN/CÀO cross-coupling of 1,2-dihalobenzene with benzamides (Scheme 1b); [8] and (iii) aromatic CÀH functionalization followed by CÀO bond formation (Scheme 1c). [9] Besides, the coordinating ability of the nitrogen has been exploited for the regioselective ortho CÀH arylation, [10] acylation, [11] hydroxylation, [12] fluorination [13] and alkenylation at the C2-aryl group of 2-aryl benzoxazoles [14] (Scheme 1d). Contrastingly, the synthesis of benzoxazole framework with CÀH functionalization at the fused-benzene ring is less literature precedent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,C hakraborti et al developed an interesting strategy for the Pd II -catalysed CÀHhydroxylation of arenes involvinghydroxylr adicalg eneratedi ns itu from 1,4-dioxane. [19] It is known that 1,4-dioxane can serve as hydroxyl radical source. [20] However,i tr equires elevated reactiont emperature (1550-2100 K).…”
Section: Catalytic Hydroxylation Of Arene Càhb Onds Using Pd/persulfatementioning
confidence: 99%
“…In 2015, Chakraborti and co-workers developed a Pd(OAc) 2 catalyzed C–H hydroxylation of 2-benzoxazolyl- and 2-benzothiazolylarenes in the presence of Na 2 S 2 O 8 as oxidant in 1,4-dioxane (Scheme 37) [66]. They also showed that other acyclic directing groups including azo, amide, anilide, carbamate and unsymmetrical urea, could also promote the ortho -hydroxylation of arenes.…”
Section: Reviewmentioning
confidence: 99%